An Investigation of Social Behaviors of Primary School Children in terms of Their Grade, Learning Disability and Intelligence Potential - (:unkn) unknown (EDAM, 2013)
In this study, to what extent 7-9-year old primary school children's' social behaviors at school vary depending on their grade, gender and learning disability was investigated. In addition, the predictive value of the intelligence scores of children with normal development and with learning disability was explored for their negative and positive behavior at school and for their academic skills. The data was collected from a total of 166 first, second and third grade primary school students, 83 of whom had a normal development process while the remaining 83 was diagnosed with learning disability. In order to identify participants' intelligence level, Wechsler Intelligence Scale for Children (WISC-R) was used and to reveal their social behavior level at school, School Social Behavior Scales which were filled in by their teachers were used. As a result of the study, it was realized that students' social competencies do not differ depending on their grade; however, the difference in terms of antisocial behavior was found to be in favor of third graders. It was also revealed that the social competence level of female students were higher than that of male students while the antisocial behaviors of the male students were found to be significantly higher than the antisocial behaviors of the female students. Besides, it was realized that social behaviors at school do not vary depending on the learning disability variable. According to the findings of the current study, children's intelligence levels have a predictive effect on their social competence, academic skills and antisocial behaviors. Moreover, the intelligence potentials of the children diagnosed with learning disability predicts their social competence and academic achievements; similarly, the intelligence potential of the children with normal development predicts their academic achievement and antisocial behaviors. As a result, it was realized that not only the activities intended to improve the academic performance of the children diagnosed with learning disability but also the activities to improve their social behavior development could be suggested. At the end of the study, the place of educational activities aiming to improve their reasoning skills through social skills education in the guidance programs at schools was discussed.
Keywords: Learning Disabilities; Intelligence Potential; School Social Behaviors; Social Behaviors; Social Competence; Antisocial Behaviors; Academic Skills